2021
DOI: 10.1007/s10693-021-00348-x
|View full text |Cite
|
Sign up to set email alerts
|

Agency Conflicts and Dividend Persistence

Abstract: Bank dividends are unusually persistent. In a crisis, they exacerbate systemic risk and raise concerns for regulators. Bank managers, however, may keep dividends elevated to mitigate agency conflicts with shareholders. One theory holds that persistent dividends may substitute for monitoring by dispersed shareholders. A second theory proposes that they attract institutional shareholders who monitor banks, mitigate agency conflicts, and seek to protect their investments' value. After controlling for regulatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 81 publications
(126 reference statements)
0
4
0
1
Order By: Relevance
“…In this paper, we extend this nascent literature by focusing on bank governance and agency conflicts when assessing the decisions by banks to pay dividends. We join other studies, such as Casey and Dickens ( 2000 ) and d’Udekem ( 2021 ), by providing empirical evidence to support the role of bank dividends in mitigating agency conflicts. Our study also complements several other studies that examine how internal governance as an alternative mechanism to mitigate agency conflicts influences bank dividends (e.g., insider ownership in Dickens et al ( 2002 ); CEO pay structure in Srivastav et al ( 2014 ); and board monitoring in Onali et al ( 2015 )).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this paper, we extend this nascent literature by focusing on bank governance and agency conflicts when assessing the decisions by banks to pay dividends. We join other studies, such as Casey and Dickens ( 2000 ) and d’Udekem ( 2021 ), by providing empirical evidence to support the role of bank dividends in mitigating agency conflicts. Our study also complements several other studies that examine how internal governance as an alternative mechanism to mitigate agency conflicts influences bank dividends (e.g., insider ownership in Dickens et al ( 2002 ); CEO pay structure in Srivastav et al ( 2014 ); and board monitoring in Onali et al ( 2015 )).…”
Section: Introductionmentioning
confidence: 79%
“…For example, Casey and Dickens ( 2000 ) show that banks increase dividends when shareholder dispersion is high in order to reduce monitoring costs. d’Udekem ( 2021 ) further posits that banks maintain their dividend payments during a financial crisis to attract institutional investors. In a similar vein, several other studies have shown that banks tend to lower their dividend payments when agency conflicts are low.…”
Section: Literature Review and Institutional Backgroundmentioning
confidence: 99%
“…The first kind of agency problem is mainly due to the scattered shareholding ratio of the principal and the lack of adequate supervision over the agent, which makes the agent often conduct opportunistic behavior based on self-interest motivation to damage the interests of the company [24]. The second type of agency problem mainly refers to the fact that the largest shareholder in the company will infringe on the interests of the company's small and medium shareholders through connected transactions, mortgage guarantees, or shareholding, based on its own higher control rights, and the private gains of control rights, to achieve the purpose of self-interest grabbing [25][26][27]. China's listed companies often have a high degree of equity concentration, compared with other countries, the second type of agency problem is more serious.…”
Section: Theoretical Analysis and Hypothesis Developmentmentioning
confidence: 99%
“…Menurut International Accounting Standards Board (IASB), pelaporan keuangan bertujuan untuk menyediakan informasi yang berguna bagi investor, kreditur, dan lainnya dalam membuat keputusan investasi, kredit, dan alokasi sumber daya [27]. Berdasarkan teori keagenan (Ross 1973), motivasi untuk menggambarkan kinerja perusahaan yang salah berakar pada konflik kepentingan antara manajer dan pemegang saham karena pemisahan kepemilikan dari manajemen [28]. Untuk meningkatkan pelaporan keuangan, direktur diperbolehkan untuk melakukan penilaian dalam mengadopsi metode pelaporan yang sesuai dengan ekonomi perusahaan; Namun, ini menghasilkan peluang bagi mereka untuk memanipulasi keuntungan.…”
Section: Tinjauan Pustaka 21 Manajemen Labaunclassified